Molecular genetic analysis of somaclonal variations in in vitro cultured vanilla planifolia Andrews - Chai, Li Chin (2019)
Somaclonal variations (SV) in micropropagated in the vanilla orchid cultivar V. planifolia Andrews are not well-studied so far. Understanding the occurrence of SV in vanilla is important for the development of an effective pre-screening tool for clonal fidelity in in vitro mass propagation of elite vanilla genotypes and for the selection process during in vitro crop improvements of vanilla, which has a narrow genetic basis due to being extensively cloned. In this research, two main regeneration systems, the direct nodal regeneration using optimal shoot induction medium (SIM, Murashige and Skoog (MS) medium + 1.0 mg/L 6-benzylaminopurine (BAP) and the indirect nodal regeneration using optimal callus induction medium (CIM, ½ MS + 2.5 mg/L α-naphthalene acetic acid (NAA) + 1.0 mg/L BAP) were established. Regenerants from both direct and indirect nodal regeneration pathways were studied at morphological, genetic, epigenetic and cytological levels. Morphological abnormalities, such as irregular leaf shape and sizes, and formation of multiple shoot apices, were observed in callus regenerants of vanilla. Further analyses at the genetic and epigenetic levels using inter-simple sequence repeats (ISSR) and methylation-sensitive amplified polymorphisms (MSAP) DNA markers also showed that the indirectly regenerated vanilla cultures were both genetically and epigenetically unstable, as opposed to the directly regenerated vanilla cultures. Using flow cytometry (FCM), relative genome size estimation of vanilla (2C = 5.5 ± 0.27 pg) was achieved with P. sativum as the internal control. Endopolyploidy was observed in different organ explants of vanilla, with irregular marginal replication ratios of 1.33 ± 0.02, 1.42 ± 0.02, 1.60 ± 0.01, 1.76 ± 0.01 and 1.69 ± 0.03 (instead of 2) between respective peaks, which is called “progressively partial endoreduplications, a unique phenomenon seen in some orchid species. The marginal replication ratio was constant between different tissues, but ploidy population levels varied among different tissues. Axillary buds have a dominant 1.5C peak and relatively smaller populations of other endopolyploidy peaks, as opposed to leaf and root and callus tissues which have a relatively balanced population of different mixoploids. Prolonged culture period of callus cultures induced from nodal bud explants (with dominant 1.5C peak) showed a mixoploid population, which increased in the polyploidy population and overall nuclear content (pg) over prolonged culture duration up to 12 months. To obtain a global view of molecular stress response to prolonged culture duration of vanilla callus culture, we further studied by conducting de novo mRNA and microRNA-seq of the 3M, 6M and 12M vanilla calli. A series of genes involved in five key gene families, namely DNA methylation family (found in the KEGG pathway of cysteine and methionine metabolism), retrotransposable element family (in particular the copia and gypsy-like LTR retrotransposons), histone modification family (in particular the HDACs and HATs), DNA transcription factors (in particular the WRKY transcription factors) and microRNAs were found to be differentially expressed. Three miRNAs, namely the vpl_miR395g, vpl_miR166r and vpl_miR8155 expressed in prolonged vanilla callus cultures, were found to potentially regulate eight genes, which fell into the functional gene families of DNA methylation and retrotransposable elements; which results were validated by qRT-PCR. This study has shown that a direct nodal regeneration method is more suitable for clonal mass propagation of elite vanilla genotypes as it produced genetically and epigenetically stable regenerants; while the indirect nodal regeneration could be a potential tool for increasing the genetic diversity of vanilla through in vitro improvements. At the transcriptional level of study, we observed the potential cross-talk between retrotransposable elements, microRNA and DNA methylation, which could have led to the epigenetic regulation of SV in vanilla callus. For clonal fidelity screening process for SV in vanilla, it is recommended to combine morphological, genetic, epigenetic and cytological methods for more effective screening. The microRNAs and their putative target genes could be potential targets for in vitro crop improvements of vanilla as well as screening tools, however, further characterization work is required.